2020
DOI: 10.3390/ijms21249663
|View full text |Cite
|
Sign up to set email alerts
|

Oxo-Titanium(IV) Complex/Polymer Composites—Synthesis, Spectroscopic Characterization and Antimicrobial Activity Test

Abstract: The emergence of a large number of bacterial strains resistant to many drugs or disinfectants currently used contributed to the search of new, more effective antimicrobial agents. In the presented paper, we assessed the microbiocidal activity of tri- and tetranuclear oxo-titanium(IV) complexes (TOCs), which were dispersed in the poly(methyl methacrylate) (PMMA) matrix. The TOCs were synthesized in reaction to Ti(OR)4 (R = iPr, iBu) and HO2CR’ (R’ = 4-PhNH2 and 4-PhOH) in a 4:1 molar ratio at room temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 65 publications
(109 reference statements)
3
25
0
Order By: Relevance
“…Analysis of the literature data shows that photocatalytic activity of TOCs can be controlled by way of ligand functionalization, especially of carboxylate groups [21]. The results of our previous research on the photocatalytic activity estimation of composites, which contained PMMA and TOCs consisting of {Ti 4 O 2 } cores, confirmed this [17,18]. According to these reports, systems stabilized with 9-fluorenocarboxylate and 4-aminobenzonate ligands exhibited the best properties.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Analysis of the literature data shows that photocatalytic activity of TOCs can be controlled by way of ligand functionalization, especially of carboxylate groups [21]. The results of our previous research on the photocatalytic activity estimation of composites, which contained PMMA and TOCs consisting of {Ti 4 O 2 } cores, confirmed this [17,18]. According to these reports, systems stabilized with 9-fluorenocarboxylate and 4-aminobenzonate ligands exhibited the best properties.…”
Section: Introductionmentioning
confidence: 62%
“…In general, the dispersion of (1) and (2) grains in PCL matrix slightly reduces the decomposition temperature of most investigated composites (2-5 • C), which can be associated with the decomposition of TOCs below 320 • C (in thermograms, the weak decomposition stage below 320 • C was found (Figure 5a). The exception was the PCL + 20(2), for which the decomposition temperature was decreased and their one-stage thermal decomposition proceeded between 260 and 420 • C. For PMMA composites, it can be seen that the decomposition process takes place in two stages, as described in the publication [18]. For comparison, TGA studies of PMMA and PMMA + 20TOCs (TOCs = (1) and ( 2)) samples revealed that addition TOCs grains decreased the first stage of thermolysis temperature and increased the second one (Figure 5c, Table 2).…”
Section: The Production Of Polymer + Tocs Composites and Studies Of Their Physicochemical And Thermal Propertiesmentioning
confidence: 93%
See 3 more Smart Citations